APPLICATION OF POWDER HIGH-SPEED STEEL AS ANTIFRICTION MATERIAL - M. Beznak; A. S. Chaus (Литьë и металлургия)
The influence of disulphide molybdenum additives on antifriction characteristics of powder high-speed steel produced by means of hot hydrostatic pressing is investigated. It is shown that disulphide molybdenum additives promote the decrease of coefficient of friction and temperature in hearth of friction as a result the increase of wear resistance of steel.